Penile Neoplasm: Diagnosis Masked by SGLT2 Inhibitors - Silva, Ana João; Guilherme Pereira, José; Cadavez, Hugo (Gazeta Médica, 2023)
Penile cancer is a rare neoplasm that can present with a wide range of symptoms. When diagnosed early, it has an excellent prognosis, however, it worsens dramatically in the presence of metastases. A 69-year-old male patient with a personal history of diabetes mellitus. After prescription of empagliflozin, the patient develops an erythematous lesion in the foreskin. He was progressively medicated with clotrimazole cream, valaciclovir, azithromycin, tinidazole, fluconazole, amoxicillin + clavulanic acid and hydrocortisone without improvement. Diagnosed with squamous cell carcinoma of the penis after biopsy in a Dermatology consultation. This is a case of penile cancer with non-specific symptoms in a patient with risk factors for genital infections, making clinical suspicion difficult and promoting the adoption of measures aimed at the treatment of genital infection. The role of the family doctor is essential for an early referral of patients with clinical signs suggestive of penile cancer.